2014
DOI: 10.1016/j.urolonc.2014.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Minimal changes in the systemic immune response after nephrectomy of localized renal masses11This work was supported by the University of Iowa Carver College of Medicine/Department of Urology Investigator Start-up Funds, NIH Grant CA181088-01 (to L.A.N.), and NIH Grant CA109446 (to T.S.G.).

Abstract: Objectives Renal cell carcinoma (RCC) is an immunogenic tumor, and multiple immunostimulatory therapies are in use or under development for patients with inoperable tumors. However, a major drawback to the use of immunotherapy for RCC is that renal tumors are also immunosuppressive. As a result, current immunotherapies are curative in <10% of patients with RCC. To better understand the systemic immune response to RCC, we performed a comprehensive examination of the leukocyte and cytokine/chemokine composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…Similarly, high serum concentrations of IL-1β and MCP-1 have been described in larger cohorts of RCC patients (57), and IL-1β levels have been shown to be an independent risk factor for increased risk of recurrence and decreased overall survival in limited stage RCC (61). …”
Section: Discussionmentioning
confidence: 93%
“…Similarly, high serum concentrations of IL-1β and MCP-1 have been described in larger cohorts of RCC patients (57), and IL-1β levels have been shown to be an independent risk factor for increased risk of recurrence and decreased overall survival in limited stage RCC (61). …”
Section: Discussionmentioning
confidence: 93%
“…Previous studies by our group and others have shown that CCL2 concentrations are elevated in the serum of RCC patients [ 18 , 30 ], and that CCL2 is produced at high levels by the tumor-associated macrophages that infiltrate human renal tumors [ 31 ]. Our murine results agree with these findings and suggest that additional cell populations should be examined in human renal tumors for their production of CCL2.…”
Section: Resultsmentioning
confidence: 99%
“…MDSCs are immature, myeloid-lineage cells that are recruited to solid tumors by local production of pro-inflammatory cytokines and chemokines [ 13 – 15 ]. Numerous studies have shown that MDSC are key contributors to tumor-associated immune suppression, and we and others have identified them in the peripheral blood and tumors of human subjects with RCC [ 16 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of multi-color flow cytometry has allowed for a more comprehensive analysis and identification of specific cellular subsets/phenotypes. Using phenotypic panels shown in Table 1, increased frequencies of at least one ‘immature’ or ‘suppressive’ myeloid subset in the peripheral blood has been identified in patients with melanoma [1622], sarcoma [21,23,24], head and neck cancer [21,2528], brain tumors [22,24,29], thyroid cancer [30], lung cancer [21,25,26,3138], breast cancer [21,25,30,31,3941], cervical and ovarian cancer [24,31], renal cell carcinoma [22,24,4245], prostate cancer [46,47], hepatocellular carcinoma [31,4850], and gastrointestinal cancers [2022,26,30,31,46,5055] (including esophagus, stomach, pancreas, bladder/urinary tract, and colorectal cancer) compared to healthy controls or patients with other non-malignant disorders. Atypical myelopoiesis has also been described in hematologic malignancies, including multiple myeloma[56], chronic lymphocytic leukemia[24], mantle cell lymphoma[57], B cell lymphoma[24], and acute myeloid leukemia (AML) or chronic myeloid leukemia (CML) [58,59].…”
Section: Introductionmentioning
confidence: 99%
“…‘Conventional’ therapies have shown transient decreases in myeloid cell populations following treatment, including surgical resection [46] or radiotherapy [104], but this may not be consistent across tumor types [42,46]. Some studies have assessed myeloid cells following conventional chemotherapy [105].…”
Section: Introductionmentioning
confidence: 99%